Clinical implementation and error sensitivity of a 3D quality assurance protocol for prostate and thoracic IMRT. (8th September 2015) - Gueorguiev, Gueorgui; Cotter, Christopher; Turcotte, Julie Catherine; Crawford, Bruce; Sharp, Gregory; Mah'D, Mufeed
Abstract : This work aims at three goals: first, to define a set of statistical parameters and plan structures for a 3D pretreatment thoracic and prostate intensity‐modulated radiation therapy (IMRT) quality assurance (QA) protocol; secondly, to test if the 3D QA protocol is able to detect certain clinical errors; and third, to compare the 3D QA method with QA performed with single ion chamber and 2D gamma test in detecting those errors. The 3D QA protocol measurements were performed on 13 prostate and 25 thoracic IMRT patients using IBA's COMPASS system. For each treatment planning structure included in the protocol, the following statistical parameters were evaluated: average absolute dose difference (AADD), percent structure volume with absolute dose difference greater than 6% (ADD6), and 3D gamma test. To test the 3D QA protocol error sensitivity, two prostate and two thoracic step‐and‐shoot IMRT patients were investigated. Errors introduced to each of the treatment plans included energy switched from 6 MV to 10 MV, multileaf collimator (MLC) leaf errors, linac jaws errors, monitor unit (MU) errors, MLC and gantry angle errors, and detector shift errors. QA was performed on each plan using a single ion chamber and 2D array of ion chambers for 2D and 3D QA. Based on the measurements performed, we established a uniform set of tolerance levels to determine if QA passes for each IMRT treatment plan structure: maximum allowed AADD is 6%; maximum 4% of any structure volume can be with ADD6 greater than 6%, and maximum 4% of any structure volume may fail 3D gamma test with test parameters 3 % / 3   mm DTA. Out of the three QA methods tested the single ion chamber performed the worst by detecting 4 out of 18 introduced errors, 2D QA detected 11 out of 18 errors, and 3D QA detected 14 out of 18 errors. PACS number: 87.56.Fc